A New Zealand regional work-related sprains and strains surveillance, management and prevention programme: study protocol - Ian Laird; Justine McIntyre; Barry Borman; Rod Adank; Liz Ashby (BMC Musculoskeletal Disorders, 2022)
Abstract Background The impact and costs associated with work-related sprains and strains in New Zealand and globally are substantial and a major occupational and public health burden. In New Zealand around one-third of all sprains and strains workers compensation (ACC) claims (2019) are for back injuries, but shoulder and arm injuries are increasing at a faster rate than other sprain and strain injuries (ACC, 2020). A need exists for a change to current approaches to sprains and strains prevention, to more effectively manage this significant and persistent problem in workplaces. Designing out hazards is one of the most effective means of preventing occupational injuries and illnesses. This paper outlines the study protocol of the surveillance, management and prevention programme and describes the utilisation of prevention through design principles in the prevention of work-related sprains and strains in agriculture/horticulture/food production in the Hawkes Bay region of New Zealand. Methods This is a prospective mixed methods study incorporating the collection of quantitative data to describe the epidemiology of work related sprains and strains injuries presenting to the regional health centre (Hastings Health Centre) over a period of 24 months and qualitative data from participants presenting at the health centre to identify high risk industry sectors/ occupations/ workplaces and tasks and design, develop and apply prevention through design principles/ solutions/interventions to critical features of the work and work environment and undertake an outcome evaluation during the last 6 months of the project. Discussion The purpose of this project is to establish an epidemiological surveillance programme to assess the incidence and prevalence of work-related sprains and strains according to age, sex, industry sector and occupation to target efforts to prevent work-related sprains and strains, by applying prevention through design (PtD) principles in selected workplaces in agriculture. The collection of more detailed case, occupational and work history data from a sample of patients presenting at the HHC clinic will identify high risk industry sectors/occupations/workplaces and tasks. Assessment techniques will include comprehensive design, design thinking and human factors/ergonomics methodologies through co-design and participatory ergonomics techniques. The PtD solutions/ interventions implemented will be evaluated using a quasi-experimental design consisting of a pre-test/ post-test with-in subjects design with control groups that do not receive the intervention.